A review of critical repeatability and reproducibility issues in powder bed fusion. (15th January 2020) - Dowling, L.; Kennedy, J.; O'Shaughnessy, S.; Trimble, D.
Abstract: Due to the many advantages associated with metal additive manufacturing (AM) processes, research into these technologies has grown significantly over the last number of years. However, repeatability and reproducibility are critical issues in AM when compared to traditional manufacturing processes. This work reviews the current state of repeatability/reproducibility in metal additive manufacturing, specifically in powder bed fusion technologies such as selective laser melting (SLM) and electron beam melting (EBM). The repeatability issues present in these AM processes is shown to be pervasive across the available literature. The additive manufacturing process is separated into pre-process, para-process and post-process stages and a critical review of the causes and impact of repeatability found at these stages is conducted. Key parameters of these stages: powder properties, laser characteristics and post-processing are studied in depth as sources of variation that can diminish repeatability. An understanding of the limitations of analysing repeatability from the current literature is developed and areas for further research towards the improvement of repeatability are identified. Graphical abstract: Unlabelled Image Highlights: An overview on the current state-of-the-art research regarding the repeatability issues in powder bed fusion processes In-depth study of potential sources of variation that give rise to the lack of repeatability in metal 3D printing Addresses the pre-process, para-process and post-process effects in the process and areas of future research